Kupi Gayo: Deixis in Ervan Ceh Kuls song lyrics - Inayah, Nurul; Achmad, Diana; Irnanda, Septhia; At'thahirah, At'thahirah (Studies in English Language and Education, 2023)
Deixis, the linguistic phenomenon of words pointing to specific entities in discourse or situational context, has been explored in various forms of expressive arts. One interesting example of deixis in expressive arts is the use of deixis in song lyrics. In this present study, Gayonese local songs from Aceh, Indonesia, in the Kupi Gayo album by Ervan Ceh Kul, are studied by examining the deictic terms he used to construct the cultural context of ten songs. For this goal, the descriptive qualitative method was used to analyze the songs deixis using the framework of Grundy (2000). The results revealed that the songwriter used more first and second personal deictic terms, suggesting that he tried to add a layer of emotional connection between the artist and the listeners, allowing for a more immersive and relatable musical experience. Nevertheless, he used place and temporal deixis less frequently, indicating that he tried to create rich and immersive experiences for the listeners. The results showed that using deictic terms in the vernacular language facilitates effective communication and understanding within a specific community or culture. By understanding the function and purpose of deixis in the vernacular language, researchers and linguists can gain insights into how individuals in a society navigate their social interactions.